AB1188 INFLUENZA VACCINATION TREND IN THE LAST DECADE AND FACTORS INFLUENCING THE RATE OF INFLUENZA VACCINATION IN CHRONIC INFLAMMATORY ARTHRITIS IN THE ITALIAN REGION OF FRIULI VENEZIA GIULIA (2006-2018). (2nd June 2020) - Quartuccio, L.; Zabotti, A.; De Marchi, G.; Gallo, T.; De Vita, S.; Valent, F.
Abstract : Background: vaccination is one of the most important medical intervention to prevent infectious complications in population at risk. EULAR recommendations for vaccination of patients suffering from autoimmune inflammatory rheumatic diseases (AIIRD) have been recently updated (1). Objectives: to verify the level of coverage of the influenza vaccination in a local population of patients suffering from rheumatoid arthritis (RA), psoriatic arthritis (PsA) or ankylosing spondylitis (AS). Methods: integration of the information coming from many administrative databases were used to this end. The Regional Health Information System of Friuli Venezia Giulia was used as the source of information for this retrospective cohort study. Patients were residents in Friuli Venezia Giulia and they had to carry the exemption code for RA, or PsA, or AS and at least one prescription of a tsDMARD or a bDMARD in the 9 months before the start of the vaccination season (from October 1 to December 31). The observation period comprises all the years from 2006 to 2018. Multivariate logistic regression was used to assess the association between the probability of vaccination and demographic and clinical patient's characteristics in the influenza season 2018-2019. Results: table 1 summarizes the results. During the whole period of observation, the coverage is always under the minimum desirable threshold of 75% and far from the optimum target of 95%, according to the National Italian Plan for Vaccination in the population at risk, even in the subgroup of older patients (age ≥ 65 years). In the logistic model including sex, age category, number and type of chronic conditions, socioeconomic status, rheumatic disease affecting the patient, area of residency, and treatment with tsDMARD or bDMARD, in 2018, older subjects were more likely to be vaccinated (people 65-74 vs 44-64, OR 4.63, 95%CI 3.76-5.70; people 75-84, OR 6.61, 95%CI 5.14-8.50) as were those with diabetes comorbidity (OR 1.64, 95%CI 1.03- 2.59); a lower borderline-significant probability of being vaccinated was observed among patients with low socioeconomic status (OR 0.83, 95%CI 0.68-1.00), and those treated by a biologic agent (OR 0.85, 95% CI 0.73-1.00) Conclusion: influenza vaccination coverage is low in a population at high risk of infectious complications, even in the subgroup of elderly patients. Local guidelines are needed to improve the vaccination policies in AIIRD in order to increase the protection among patients who really need it. References: [1]Furer V, et al. Ann Rheum Dis 2019. Ann Rheum Dis. 2019 Aug 14. pii: annrheumdis-2019-215882 Disclosure of Interests: Luca Quartuccio Consultant of: Abbvie, Bristol, Speakers bureau: Abbvie, Pfizer, Alen Zabotti Speakers bureau: Celgene, Novartis, Janssen, Ginevra De Marchi: None declared, Tolinda Gallo: None declared, Salvatore De Vita Consultant of: Roche, GSK, Speakers bureau: Roche, GSK, Novartis, Francesca Valent: None declared